Memahami Gaya Belajar Siswa: Kunci Keberhasilan Personalisasi Pembelajaran - Rindu Amelia; Salwa Nala Rohmatal Izzah; Marisa Amalia Hikmah; M. Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2025)
This research discusses the importance of understanding students' learning styles as a key to personalizing education. Learning styles, which can be divided into three main categories: visual, auditory and kinesthetic, affect the way students absorb and understand information. Students with visual learning styles find it easier to understand material through vision, auditory students are more effective in learning through their hearing, while students with kinesthetic learning styles are more prominent in physical activities and hands-on interactions. This research emphasizes the need for educators to recognize and adapt teaching methods to students' learning preferences to improve engagement, motivation and academic outcomes. It also discusses the challenges in implementing personalized learning, such as the difficulty in identifying the right learning style and the risk of over-focusing on a particular learning style. The method in this research uses literature review by analyzing existing data regarding learning styles and their implications for personalized learning. Thus, this research is expected to provide insights for educators in designing teaching strategies that are more effective and responsive to students' individual needs